2009
DOI: 10.1002/jbm.b.31312
|View full text |Cite
|
Sign up to set email alerts
|

Medical‐grade silicone induces release of proinflammatory cytokines in peripheral blood mononuclear cells without activating T cells

Abstract: For more than 40 years, silicone implants had been employed in aesthetic, cosmetic medicine, and plastic surgery. Although adverse reactions produced by these products are rare, cases of immuno-mediated reactions have been reported. To evaluate the aspects of immuno-reactivity to medical-grade silicone dermal filler, peripheral blood mononuclear cells (PBMC) of 39 individuals were studied. PBMC used include individuals with silicone injection-related delayed adverse reactions, with silicone injections, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
2
32
1
Order By: Relevance
“…In spite of that, antibiotics are used as a treatment of this kind of medical complications though the role of antibiotics either as anti-inflammatory or bactericidal drugs is disputable. Although we were not able to demonstrate their anti-inflammatory effect in two previous in vitro studies [21,22], other authors obtained different results. Webster et al [34], in an elegant study, showed that tetracyclines and ciprofloxacin dose-dependently inhibited granuloma formation in vitro.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In spite of that, antibiotics are used as a treatment of this kind of medical complications though the role of antibiotics either as anti-inflammatory or bactericidal drugs is disputable. Although we were not able to demonstrate their anti-inflammatory effect in two previous in vitro studies [21,22], other authors obtained different results. Webster et al [34], in an elegant study, showed that tetracyclines and ciprofloxacin dose-dependently inhibited granuloma formation in vitro.…”
Section: Discussioncontrasting
confidence: 52%
“…There is no doubt that biomaterials may provoke local or systemic chronic granulomatous immune-mediated reactions in some individuals [1,7,8,9,12,16,18,19,20,21,22]. The exact cause of these adverse effects is elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra of some sample showed additional ionic series, typically in the low-mass range of the spectra. For example, the DART spectrum of the NUK Happy Days pacifier reveals the release of some low-mass polyethylene glycols that are detected as [PEG + NH 4 ] + ions (Figure 3). This spectrum has been recalibrated internally on silicone signals in the range of m/z 684 to 1202 prior to formula assignment to the additional compounds.…”
Section: Release Of Additional Compoundsmentioning
confidence: 99%
“…However, when studied, the long-term exposure of humans to silicones was found to induce adverse health effects. For example, adverse health effects of silicones released under physiological conditions from breast implants are discussed in the context of breast cancer [1], fibrosis [2], autoimmunity [3], and inflammatory processes [4]. Nonetheless, the use of PDMS and related silicones stills seems to increase and silicone has even been suggested as a potent absorbing material for 3-alkyl-methoxypyrazine responsible for undesirable aromas in wine [5].…”
mentioning
confidence: 99%